Delevolpment of semi active suspension system - Mohammed Ragab, Ahmed (2017)
The suspension of the car plays a very important role in the safety and the comfort of the vehicle and for absorbing the shock waves and give comfort for the driver and passenger. There are different classifications of suspension, which are passive, semi-active and active suspension. There is potential for improve the model of the shock absorber, by developing electronically controllable semi active shock absorber. However, semi-active absorber been chosen for modification due better efficiency and providing different characteristic of damping ratio when compares to the passive shock absorber and low cost when compare with active shock absorber. Therefore, a controller was developed to be attached with the absorber to the control the degree of softness and hardness. The level of softness and hardness of shock absorbers play an important role in giving comfort to the driver and passengers while driving. The level of hardness can be changed by controlling the flow of hydraulic oil flow in the shock absorbers between piston during the process of compression and rebound. There will be a control unit to control the damping ratio. It adjusted to 4 different levels of hardness. The modifications on inner parts of the shock absorber was done to meet the requirements of the design. Several test procedures have been chosen to evaluate the dynamic behavior of the vehicle. The tests were done bumpy, straight line and roundabout road, these tests used to make objective measurements for evaluation of the acceleration and ride quality performance. Data was analyzed in effectiveness on vehicle acceleration. Ride quality and comfort was considered as well. the result shows the range is fallen in area of little uncomfortable.